INTERNALIZING THE MORAL PRINCIPLES OF RAMAYANA’S SCRIPTURE TO PREVENT THE POP CULTURE’S IMPACT - I Made Arsa Wiguna; Putu Sanjaya; I Gusti Made Widya Sena (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This research is a text study of the Ramayana’s scripture to identify and analyze the moral principles in it in regards to prevent the pop culture’s impact. The method used in this paper is close reading and content analysis. Popular culture influences the mindset, habits and moral behavior of society. Pragmatic, hedonistic, consumerist behaviors, and fear of missing out are symptoms of addiction to popular culture. The trend of self-destruction seems more interesting than the trend of building self-quality. The massive spread of popular culture through social media and other social platforms needs to be anticipated, one of which can be done through the integration of moral values as a learning materials in school sourced from religious teachings. Ramayana’s scripture, which contains many moral teachings, can be a universal reference in preventing the negative impacts of popular culture. The moral principles in question are the principles of good attitudes, justice and respect for ourself. Apart from that, strong moral personality attitudes include honesty, authentic values, willingness to take responsibility, moral independence, moral courage, humility, being realistic and critical. These moral principles are found in most of the kanda, and should be actualize as a filtration of popular culture's impact.